Deep exploration of PARP inhibitors in breast cancer: monotherapy and combination therapy - Chen, Zheling (J Int Med Res, 2021)
OBJECTIVE: Nearly 5% of patients with breast cancer carry germline BRCA mutations, which are more common in triple-negative breast cancer (TNBC). Previous clinical trials demonstrated the therapeutic efficacy of poly (ADP-ribose) polymerase inhibitors (PARPis) against BRCA-mutated metastatic breast cancer. The current study conducted a systemic review and meta-analysis of the clinical efficiency and safety of PARPis, either alone or combined with chemotherapy, in patients with TNBC. METHODS: We searched PubMed, EMBASE, and ClinicalTrials.gov to identify randomized controlled trials comparing PARPi therapy with chemotherapy, and comparisons of chemotherapy plus PARPis with chemotherapy alone were included. The study endpoints included the clinical response, progression-free survival, and adverse event rates. RESULTS: PARPi therapy was revealed to improve progression-free survival in patients with advanced breast cancer, either alone or in combination with chemotherapy. Subgroup analysis illustrated that patients with mutant BRCA1 and mutant BRCA2 and those who had not been treated with platinum-based agents could specifically benefit from PARPis. CONCLUSION: PARPi monotherapy can significantly improve clinical outcomes in patients with advanced breast cancer, especially those with TNBC, those who had not previously received platinum therapy, and those with mutant BRCA1/2. PARPis combined with chemotherapy represent new treatment options for patients with advanced cancer.